مراقبة توتر قضبان تجميع شبكة نقل الطاقة الكهربائية السورية باستخدام خرائط كوهونين العصبونية ذاتية التنظيم ذات التعليم المراقب - حيدر, تمام; شعبان, فيصل; الخير, الحسين (Latakia University Journal -Engineering Sciences Series, 2018)
This paper presents the usage of a type of neural networks called Kohonen Supervised Self-Organizing Maps SSOM for security assessment of Syrian power transmission system by monitoring buses voltage. With the increase in load demand, the network is loaded to its limits making it vulnerable to black out when facing a disturbance (load changes, generator outages, transfer lines outages and load loss). All energy management systems work to obtain economic and secure operation of power system, so we have to determine whether this system is secure or insecure in the static state. This paper presents a graphical user interface GUI to the system operator with the state (secure or insecure) of stations in the Syrian power transmission network under normal and abnormal conditions. We used a new modification called Batch-Training Algorithm presented by Kohonen in his book "Self-Organizing Maps", this modification is used to train the Kohonen neural network in supervised manner that gives the network more stability and makes it able to deal with large electrical networks like the Syrian Transmission network, the case study used in this paper. Simulation studies showed that this method gives accurate and fast results compared with traditional methods such as fast-decoupled Newton Raphson. نستخدم في هذا البحث شبكات كوهونين العصبونية ذاتية التنظيم ذات التعليم المراقب Kohonen Supervised Self-Organizing Maps SSOM لتقييم أمان شبكة نقل الطاقة السورية عن طريق مراقبة توترات قضبان التجميع لهذه الشبكة. حيث أنه مع زيادة الطلب على الطاقة تعمل أنظمة القدرة عند حدود تشغيل قريبة من الحدود العظمى المسموحة مما يجعلها معرضة في أية لحظة لحدوث حالة تعتيم جزئي أو عام عند تعرضها لاضطراب معين (تغيرات في الاحمال- خروج محطات توليد- خروج خطوط نقل- فقدان أحمال أو محطة تحويل). تعمل جميع أنظمة إدارة الطاقة لتحقيق تشغيل اقتصادي آمن لنظام القدرة، ومن أجل الوصول للتشغيل الاقتصادي يجب تحديد إذا كان هذا النظام آمن أو غير آمن في حالته الستاتيكية. يقدم هذا البحث واجهة بصرية لمشغل النظام تبين محطات الشبكة السورية مع تبيان حالة هذه المحطات (آمنة/غير آمنة) بحيث يظهر الخرج على شكل فئات Classes حسب حالة المحطة. وقد أظهرت هذه الطريقة سرعة كبيرة مقارنة مع الطرق التقليدية (سريان الاستطاعة) كما أننا استخدمنا تعديل جديد لشبكات كوهونين العصبونية ذاتية التنظيم وهو تدريبها بشكل مراقب Supervised Learning وهو التعديل الذي قدمه العالم كوهونين في كتابه Self-Organizing Maps وأسماه Batch-Training Algorithm. مما جعل التدريب أكثر استقراراً وجعل شبكات كوهونين العصبونية أكثر قدرة على التعامل مع الشبكات الكبيرة كنظم القدرة المعقدة كما هو حال الشبكة السورية موضوع هذه الدراسة، وجعل شبكات كوهونين العصبونية مناسبة جداً لتطبيقات أمان نظام القدرة Power System Security.